MONITORING AND DETECTION SYSTEM OF NUTRITION FLUID CONCENTRATION AND TEMPERATURE CONDITION AT HYDROPONIC PLANTING PROCESS - Abdullah Abdullah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2019)
Monitoring and detection system of nutrition fluid concentration and temperature condition is very needed to process hydroponic planting, nutrition fluid concentration and temperature is important variable to determine result plant of hydroponic. The value of nutrition fluid concentration and temperature which is not appropriate can be sure of crop failure. The system can detect and monitor nutrition fluid concentration and temperature at the plant. So that if two variables is not in the right condition, there will be a notification in the form of an alarm and warning to be displayed to LCD, so that the problem of the condition of faulty nutrition and the need for improper temperatures can be overcome. The research used Temperature sensor DHT11 who can sense temperature object where the output is an analog output that must be converted into digital data so that it can be processed by the microcontroller, TDR sensor (Total Dissolve Solid) which can know nutrition fluid concentration while the TDS value high so the fluid is turbid, vice versa. The function of microcontroller Atmega328 as a centre processing for all data (input/output) and equipped with 4 x 20 cm2 LCD display output. So the information of the result measurements and other information can be seen clearly on the LCD display.  The result of the analysis proved that sistem had inregrated successfully and reach target who expectation is the sistem can used to monitor and detect sistem of nutrition fluid concentration and temperature condition at hydroponic planting process.Keywords: concentration, fluid,  hydroponic, nutrition,  and temperature.